2012
DOI: 10.1111/j.1365-2702.2012.04236.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐tailored self‐management intervention for older adults with hypertension in a nursing home

Abstract: A patient-tailored intervention is feasible not only to empower nursing home residents with hypertension for their care, but also to offer a qualified training and guidelines to nursing home staffs, expanding their professional competence in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 47 publications
(115 reference statements)
3
38
2
3
Order By: Relevance
“…The settings in which the studies took place varied. The majority of the studies used group-based activities in community or faith based centers; two used a home-based intervention [11] [40] and one a nursing home [32]. One large interventional study utilized multiple locations for self-management programs over 17 states [41].…”
Section: Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The settings in which the studies took place varied. The majority of the studies used group-based activities in community or faith based centers; two used a home-based intervention [11] [40] and one a nursing home [32]. One large interventional study utilized multiple locations for self-management programs over 17 states [41].…”
Section: Population Characteristicsmentioning
confidence: 99%
“…Bandura linked role modeling to encouraging behavior change [24] [25]. Two studies focused either upon personal interactions in the home setting or did not use a group format [11] [40], one used individualized training in a nursing home [32]; the remaining studies used a variation of group observational learning.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Also, Park et al [35] illustrated that their study did not show any relationship between stress and high triglyceride levels.…”
Section: 4mentioning
confidence: 99%
“…This may be due to providing emotional support to the patient through continuing social interaction with the researcher, encouraging the patient to cope with his illness through education, an learning relaxation techniques and assertiveness training.These results are in line with Theodorou et al, [27] who found significant improvement in all dimensions of the QOL in follow-up measurements. Moreover, Park et al [35] found that health education and individual counseling was significantly effective in improving blood pressure, self-care behaviors, exercise self-efficacy, and medication compliance of hypertensive residents at a nursing home. Also, Mersal et al [36] reported that self-efficacy was significantly improved among a study group after implementation of lifestyle guidelines than control group.…”
Section: 5mentioning
confidence: 99%
“…Most studies examining the efficiency of hypertension self-care activities have concentrated on medication adherence, physical exercise, and a generally-appropriate diet (Warren-Findlow & Seymour, 2011;Park et al, 2012); few have focused on reducing salt intake. Medication use without diet change, including salt reduction, cannot control hypertension (DeSimone & Crowe, 2009).…”
Section: Introductionmentioning
confidence: 99%